Lipid profiling of cyanobacteria Synechococcus sp. PCC 7002 using two‐dimensional liquid chromatography with quadrupole time‐of‐flight mass spectrometry. Issue 19 (9th September 2016) - Shan, Yabing; Liu, Yiqun; Yang, Li; Nie, Honggang; Shen, Sensen; Dong, Chunxia; Bai, Yu; Sun, Qing; Zhao, Jindong; Liu, Huwei
Abstract : Glycerolipid is a main component of membranes in oxygenic photosynthetic organisms. Up to now, the majority of publication in this area has focused on the physiological functions of glycerolipids and lipoprotein complexes in photosynthesis, but the study on the separation and identification of glycerolipids in thylakoid membrane in cyanobacteria is relatively rare. Here we report a new method to separate and identify five photosynthetic glycerolipid classes, including monoglucosyl diacylglycerol, monogalactosyl diacylglycerol, digalactosyl diacylglycerol, sulfoquinovosyl diacylglycerol, and phosphatidylglycerol, in cyanobacteria Synechococcus sp. PCC 7002 by two‐dimensional (normal‐ and reversed‐phase) liquid chromatography online coupled to quadrupole time‐of‐flight mass spectrometry. Over twice as many lipid species were detected by our method compared to the previously reported methods. Ten new odd‐chain fatty acid glycerolipids were discovered for the first time. Moreover, complete separation of isomers of monogalactosyl diacylglycerol and monoglucosyl diacylglycerol was achieved. According to the tandem mass spectrometry results, we found that the head group of monoglucosyl diacylglycerols was not as stable as that of monogalactosyl diacylglycerols, which might explain why the organism chose monogalactosyl diacylglycerols and digalactosyl diacylglycerols instead of monoglucosyl diacylglycerols as the main content of the photosynthetic membranes in the history of evolution. This work will benefit further research on the physiological function of glycerolipids.